Relationship between caries indexes and obesity in a sample of Puerto Rican adolescents - Lydia M. Lopez del Valle; Mariely Nieves-Plaza; Sona Rivas-Tumanyan; Rosana Hanke-Herrero (Frontiers in Dental Medicine)
BackgroundObesity and caries have become increasingly prevalent. As of yet, research results on the relationship between obesity and caries in children and adolescents have been inconclusive. This study aimed to evaluate the association between caries and obesity in adolescents.MethodsThis was a cross-sectional study of a convenience sample of 187 Puerto Rican adolescents aged 13–19 years, attending, among them, five high schools. Each participant received dental exams for caries using the criteria of the International Caries Detection and Assessment System (ICDAS), had his or her body mass index (BMI) determined, and took a 19-item risk factor questionnaire. The Significant Caries (SiC) index (for DMFT) was calculated to compare obese and healthy adolescents. Statistical analysis was performed using descriptive and inferential statistics.ResultsNearly 60% of the sample population was female, with a mean age of 15.7 (±1.25). The mean BMI percentile was 72.24 (±28.78); 48.66% of the participants had a healthy weight, 19.79% were overweight, and 30.48% were obese. Dental caries was observed in 68% of the participants; the mean caries index D3-6MFS was 5.17(±5.92) and the mean D3-6MFT was 3.59 (±3.97). No significant differences were found between caries indexes and obesity status (P > 0.05). The median (p25, p75) SiC index among overweight/obese adolescents was 9.5 (7, 12), whereas for healthy weight/underweight participants was 7 (5, 8) (p < 0.005).ConclusionsBased on the limited number of participants, no association was found between dental caries (D3-6MFS and D3-6MFT) and obesity (BMI) among adolescents.